ANALISIS PERMINTAAN DAN PENAWARAN KREDIT PERBANKAN DI INDONESIA - Dewi Lusianita; Muhammad Basir Kimin; Suhel Suhel (Department of Development Economics, Universitas Sriwijaya, 2005)
This research is about the credits of bank especially working capital credits so the title of this research is